A new species of tooth-carp, Aphanius mesopotamicus, from Iran and Iraq (Actinopterygii, Cyprinodontidae) - Brian Coad (ZooKeys, 2009)
A new species of tooth-carp, Aphanius mesopotamicus (Cyprinodontidae), is described from southern Mesopotamia in Iran and Iraq. It is distinguished from related species by pigmentation (males have clear margins to the unpaired fins, no bars on the caudal fin and 10–15 clearly defined flank bars; females bear irregular blotches or spots on the flank), distribution, and a suite of morphometric and meristic characters in multivariate space (pectoral fin rays, caudal peduncle length, scales to pelvic fin and postorbital length in males and pectoral fin rays, scales to dorsal fin, predorsal length and total scales in females). The description is based on museum specimens and there have been no recent collections of the new taxon.